Unsicherheit in Zeiten gesellschaftlicher Transformation: zur Entwicklung und Dynamik von Sorgen in der Bevölkerung in Deutschland - Jörg Dittmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
– The following study describes for Germany the development of subjective insecurity for the last 25 years. The analyses are focused on war and crime, labor and economy, and finally environment. These domains are often discussed in the context of transformation. Based on the data of the Socio-Economic Panel (SOEP) this paper not only covers the question how feelings of insecurity have changed in society over time but also includes the dynamics of change at the individual level. In addition the connection between feelings of insecurity and other indicators of well being will also be scanned. What kind of concerns affects life satisfaction and how negatively is the impact of very high concerns on individual well-being when these feelings of insecurity have frequently occurred?
Keywords: J17; F52; H41; 330; Well being; transformation; insecurity; SOEP